Integron gene cassettes and degradation of compounds associated with industrial waste: the case of the Sydney tar ponds. - Jeremy E Koenig (Public Library of Science (PLoS), 2009)
Integrons are genetic platforms that accelerate lateral gene transfer (LGT) among bacteria. They were first detected on plasmids bearing single and multiple drug resistance determinants in human pathogens, and it is abundantly clear that integrons have played a major role in the evolution of this public health menace. Similar genetic elements can be found in nonpathogenic environmental bacteria and in metagenomic environmental DNA samples, and it is reasonable to suppose that integrons have facilitated microbial adaptation through LGT in niches outside infectious disease wards. Here we show that a heavily impacted estuary, exposed for almost a century to products of coal and steel industries, has developed a rich and unique cassette metagenome, containing genes likely to aid in the catabolism of compounds associated with industrial waste found there. In addition, we report that the most abundant cassette recovered in this study is one that encodes a putative LysR protein. This autoregulatory transcriptional regulator is known to activate transcription of linked target genes or unlinked regulons encoding diverse functions including chlorocatechol and dichlorophenol catabolism. Finally, only class 1 integrase genes were amplified in this study despite using different primer sets, and it may be that the cassettes present in the Tar Ponds will prove to be associated with class 1 integrase genes. Nevertheless, our cassette library provides a snapshot of a complex evolutionary process involving integron-meditated LGT likely to be important in natural bioremediation.